Interaction of Chlamydia psittaci reticulate bodies with mouse peritoneal macrophages. - Brownridge, E (1979)
Noninfectious reticulate bodies of Chlamydia psittaci are readily phagocytized by thioglycolate-elicited mouse peritoneal macrophages in monolayer culture. The internalized reticulate bodies are rapidly destroyed as indicated by a 60 to 70% decrease in trichloroacetic acid-precipitable radioisotopic counts in the macrophage pellet by 10 h and a concomitant increase of the trichloroacetic acid-soluble radiolabeled chlamydial nucleic acid in the cytoplasm. This intracellular destruction of reticulate bodies in macrophages is independent of the multiplicity of infection. Reticulate bodies at a high multiplicity of infection, up to 1,000:1, are also incapable of inducing immediate cytotoxicity in macrophages as evidenced by the lack of early release of the host cell-soluble cytoplasmic enzyme lactic dehydrogenase. Thus, it appears that the virulence factors for (i) initiation or maintenance of intracellular survival via circumvention of phagolysosome formation and (ii) host cell damage are either missing or not expressed by the RB form of this bacterium.